Estimation of Docetaxel in Parenterals by RP-HPLC - Naresh Kumar, K.; Appala Raju, N.; Satyanarayana Raju, S.; Ramarao, B.; Mukkanti, K. (Asian Journal of Chemistry, 2010)
A simple, precise, rapid and accurate reverse phase HPLC method developed for the estimation of docetaxel in parenterals dosage form. A Unison YMC C18, 250 mm × 4.6 mm i.d., 5 μm particle size, with mobile phase consisting of acetonitrile and 0.02 M ammonium acetate in water (pH 4.5 adjusted with orthophosphoric acid) in the ratio of 45:55 v/v was used. The flow rate was 1.5 mL/min and the effluents were monitored at 230 nm. The retention time was 5.82 min. The detector response was linear in the concentration of 1-200 mcg/mL. The respective linear regression equation being Y = 46487x - 36391. The limit of detection and limit of quantification was 0.03 and 0.09 mcg/mL, respectively. The percentage assay of docetaxel was 99.09 %. The method was validated by determining its accuracy, precision and system suitability. The results of the study showed that the proposed RP-HPLC method is simple, rapid, precise and accurate, which is useful for the routine determination of docetaxel in bulk drug and in its pharmaceutical dosage form.